Quantum decoherence effects on precision measurements at DUNE and T2HK - (:unkn) unknown (My University, 2024)
We investigate the potential impact of neutrino quantum decoherence on the precision measurements of standard neutrino oscillation parameters in the DUNE and T2HK experiments. We show that the measurement of δCP, sin2⁡θ13 and sin2⁡θ23 is stronger ...
Keywords: Decoherencia cuántica; Mediciones de precisión